Circulating Extracellular Vesicles and Particles Derived From Adipocytes: The Potential Role in Spreading MicroRNAs Associated With Cellular Senescence - Siqueira, Ionara Rodrigues; de Souza Rodrigues, Andressa; Flores, Marina Siqueira; Vieira Cunha, Eduarda Letícia; Goldberg, Madeleine; Harmon, Brennan; Batabyal, Rachael; Freishtat, Robert J.; Cechinel, Laura Reck (Frontiers in Aging, 2022)
Aging is associated with adipose tissue dysfunction and is recognized as a risk factor for shortened lifespan. Considering that in vitro findings have shown the involvement of microRNA in extracellular vesicles and particles (EVPs) on senescence, we hypothesized that circulating EVPs derived from adipocytes can be involved to the aging process via their microRNA cargo. Our aims were to determine the microRNA profiles of circulating EVPs derived from adipocytes (FABP4+) from aged and young adult animals and to perform in silico prediction of their downstream signaling effects. Plasma was obtained from Wistar rats (3 and 21 months old) and adipocyte-derived EVPs were isolated. Fatty acid-binding protein 4 (FABP4) was used for adipocyte-derived EVPs isolation; microRNA isolation and microarray expression analysis were performed. The analysis revealed 728 miRNAs, 32 were differentially between groups (p<0.05; fold change ≥ |1.1|), of which 15 miRNAs were up-regulated and 17 were down-regulated in circulating EVPs from aged animals compared to young adults. A conservative filter was applied and 18 microRNAs had experimentally validated and highly conserved predicted mRNA targets (2,228 mRNAs). Canonical pathways, Disease & Functions, and Upstream Regulator analyses were performed using IPA-Qiagen, allowing a global and interconnected evaluation. IPA categories impacted negatively were Cell Cycle, Cellular Development, Cellular Growth and Proliferation, and Tissue Development, while positively were “Digestive system cancer” and “endocrine gland tumor”. Interestingly, the up-regulated miRNA15b-5p targets several cyclins, such as CCND1 and CCND2, and miR-24-3p seems to target CDK4 (cyclin-dependent kinase 4), then potentially inhibiting their expression, both miRNAs can induce a negative regulation of cell cycle progression. In contrast, silencing of negative cell cycle checkpoint regulators, such as p21 and p16, can be predicted, which can induce an impairment in response to genotoxic stressors. In addition, predicted targets, such as SMAD family members, seem to be involved in the positive control of Digestive and Endocrine tumors. Taken together, this exploratory study indicates that miRNA signature in circulating adipocyte-derived EVPs may be involved with the double-edged sword of cellular senescence, including irreversible proliferation arrest and tissue-dependent cancer, and seems to be suitable for further validation and confirmatory studies.